Infanticídio entre as abordagens jurídica e psicológica: Estudo de direito comparado - Bittencourt, Ana Carolina de Carvalho Pacheco (2014)
This study stems from the observation of the fact that infanticide, a topic which touches many areas including psychology and law, has not been sufficiently discussed in a multidisciplinary matter, leaving some knots to be undone in relation to its definition through clinical and/or forensic evaluation, tools which are extremely valuable to think about the application of law on issues in which the subjectivity of the individual is crucial. The decision to include a specific topic about comparative law is intended to demonstrate how independently of the cultural differences, it is a matter related to a social structure of essentially patriarchal power. Observing the several legal systems around the world, it is noted that they divide into two major groups, those which legislate on the base of the honoris causa criteria, and those which rely on the psicophysic criteria. If the first one makes it clear the precarious situation in which women whose life is confused with honor live, the second enchances the dicotomy between rational man, therefore strong, versus emotional woman, therefore weak. How infanticide is dealt with today by brazilian law, it is up to forensic psychology to act as to provide the most accurate and reliable reports.